Arabidopsis AMINO ACID PERMEASE1 Contributes to Salt Stress-Induced Proline Uptake from Exogenous Sources - Wang, Ting; Chen, Ying; Zhang, Min; Chen, Jiugeng; Liu, Jie; Han, Huiling; Hua, Xuejun (Frontiers in Plant Science, 2017)
Stress-induced proline accumulation in plants is thought to result primarily from enhanced proline biosynthesis and decreased proline degradation. To identify regulatory components involved in proline transport, we screened for Arabidopsis thaliana T-DNA mutants with enhanced tolerance to toxic levels of exogenous proline (45 mM). We isolated the proline resistant 1-1 (pre1-1) mutant and map-based cloning identified PRE1 as AMINO ACID PERMEASE1 (AAP1, At1g58360), which encodes a plasma membrane-localized amino acid permease. AAP1 expression is induced by salt stress and abscisic acid, but not by proline. In pre1-1 mutants, a 19-nucleotide deletion in the AAP1 coding region produced a premature stop codon. When grown on proline-containing medium, pre1-1 mutants accumulated significantly less proline than did the wild type. Under salt stress, proline uptake decreased significantly in pre1-1 mutants. By contrast, proline uptake increased significantly in the wild type. These results suggest that AAP1 functions in the increase of proline uptake during salt stress. In addition, proline uptake promotes salt tolerance in Arabidopsis seedlings. We conclude that plants can increase proline accumulation by AtAAP1-mediated proline uptake from exogenous source, which help to improve the salt tolerance of seedlings.